Unsiloed agroforestry research and policy: Livelihood and multifunction as chestnut (Castanea sativa) management priorities for Türkiye - Wall, Jeffrey; Okan, Taner; Köse, Coskun; Köse, Nesibe; Aksoy, Elif Basak (ELSEVIER, 2025)
In this study, we investigate variation in the priorities for the chestnut tree held by stakeholders across T & uuml;rkiye in order to highlight the importance of unsiloed research and policy in the study area and beyond. We designed our study to evaluate the operating hypothesis of state agencies who manage the tree in sharp regional contrast, with the western provinces managed overwhelmingly for horticulture, and the northern provinces for silviculture. We utilized ethnobiological methodologies of plant trait preference cataloguing and freelisting to engage and analyze the priorities for chestnut trees for 96 stakeholder households across T & uuml;rkiye 's chestnut suitable territory. We found that no household utilized the tree for one purpose only, that every household used the tree for both its fruits and its timber, and that the vast majority utilized the tree for nuts, timber and one other category of use. We explored the resulting data using saliency analysis, multiple correspondence analysis and geospatial visualization through inverse distance weighting. We found no significant effect of western or northern location on priorities. Our findings substantiate conservation and livelihood development theories which advocate for unsiloed, interdisciplinary research informed by stakeholders, and also showcase an application of agroforestry as a framework for directly amplifying the priorities of livelihood practitioners in the formulation of land use policy. Insights generated by this study support recommendations for T & uuml;rkiye and beyond, including more thoroughly interdisciplinary research to perpetuate multifunctional use of trees as well as more regional and unified governmental strategies for conservation and rural livelihood viability.